PROBLEM BASED LEARNING BERBANTUAN E-MAGAZINE DALAM PEMBELAJARAN IPA MATERI SISTEM PENCERNAAN DI SEKOLAH DASAR - Nikita Hoirun Nisak; Ade Cyntia Pritasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the significant effect of using the Problem Based Learning model assisted by CERNA e-magazine on the cognitive learning outcomes of IPA of grade V students of SDN Gunung Sekar 2 Sampang. This research is quantitative research with experimental research type, the research design used is quasi experimental design, and the form of research design used is non-equivalent control group design. The population in the study was the entire fifth grade of SDN Gunung Sekar 2 Sampang, totaling 66 students. The sample used in the study was the fifth grade of SDN Gunung Sekar 2 Sampang which consisted of 32 students in class V-A and 34 students in class V-B. The sampling technique in the study used nonprobability sampling with sampling purposive. The data collection techniques in this study used observation and learning outcome tests. The test instrument used in this study was first tested for validity, reliability, level of difficulty, and distinguishing power. The pre-requisite tests used are normality test and homogeneity test. Hypothesis testing using independent sample t-test. All tests in this study were calculated with the help of IBM SPSS 22. Based on the results of the independent sample t-test data analysis, the sig (2-tailed) value obtained was <0,001< 0,05, so Ho was rejected. So it can be concluded that there is an effect of Problem Based Learning model assisted by CERNA e-magazine on the cognitive learning outcomes of IPA of fifth grade students of SDN Gunung Sekar 2 Sampang.